الكفايات المهنية وعلاقتها بفعالية الذات لدى مستشاري التوجيه والإرشاد المدرسي والمهني - فليون، حنان (University Of Eloued جامعة الوادي, 2025)
هدفت الدراسة الحالية إلى معرفة العلاقة بين الكفايات المهنية وفَعالية الذات لدى مستشاري التوجيه والإرشاد المدرسي والمهني بولاية الوادي وورقلة، تكون مجتمع الدراسة من(271) مستشارا ومستشارة، واعتمدت الدراسة على المنهج الوصفي بأسلوبيه الإرتباطي والمقارن، و تم استخدام مقياسين، مقياس الكفايات المهنية المصمم من طرف الطالبة المكون من (28) فقرة، ومقياس فعالية الذات لـ (Chung&Fang,Yang)(2010) المكون من(17) فقرة. وقد أسفرت الدراسة عن النتائج التالية: - يتميز أغلبية مستشاري التوجيه والإرشاد المدرسي والمهني بمستوى كفايات مهنية منخفض. - يتميز أغلبية مستشاري التوجيه والإرشاد المدرسي والمهني بمستوى فعالية ذات منخفض. - لا توجد علاقة إرتباطية دالة إحصائيا عند مستوى الدلالة ( ) بين الكفايات المهنية وفعالية الذات لدى مستشاري التوجيه والإرشاد المدرسي والمهني. - لا توجد فروق دالة إحصائيا عند مستوى الدلالة( ) بين مستشاري التوجيه والإرشاد المدرسي والمهني على مقياس الكفايات المهنية تعزى لأقدمية العمل والتخصص الدراسي والتفاعل بينهما Abstract The given study are targeted to distinguish the link between the professional competence and the ability of swain-self at the pedagogical and professional responsible in EL Oued and Ouargla – Societal study has comprised (271) chancellor has been chosen by limiting then generally when the study has attempted a descriptive method by its linking and comparative style . tow modules has been adapted by the student:(28) paragraphs efficiency to (2010) – Chung and fang yang containing (17) paragraphs. This study has shown the next results: - most of guidance counselor school and professional training has a low of professional competencies . - most of guidance councilor for school and professional training has a low of effectiveness level . - There is no relation between the level of guidance competence and follow up competence . - There is no statistical function differences at significance level between guidance conselez and school and vocational guidance within professional competency scale is referred to word seniority and specialization. - there is no stoical differences at significance level between guidance councilor and school guidance to professional competency scale that refers to work seniority academic specialization and the interaction between them .
دراسة ميدانية بمركزي التوجيه والإرشاد المدرسي والمهني لولاية الوادي وولاية ورقلة
Thesis
Keywords: الكفايات المهنية; فعالية الذات; مستشاري التوجيه والإرشاد; مستشاري التوجيه والإرشاد المدرسي والمهني; Professional skills; Self-efficacy; School and career guidance and counseling advisors